Using the Programming Language in C++ in the Numerical Integration of Functions - Vladimirovna, Kadirova Lena (European Journal of Life Safety and Stability (2660-9630), 2023)
Observing the processes of the real world, we first describe them verbally, trying to understand the essence of phenomena, then we build mathematical models. However, we do not want to limit ourselves to building formal models, but we want to get a qualitative and quantitative idea of the processes under study, to see them on graphs.